IMPLEMENTATION OF ISLAMIC ENTREPRENEURSHIP IN BUILDING BUSINESS VENTURES IN PESANTREN SIDOGIRI - Miswatun hasanah; Nurul Huda (SEAN Institute, 2023)
Economic activity in Islam (Islamic Entrepreneurship) is an integral part of the conception of the balance of life between the world and the hereafter. As a consequence of this concept, an Islamic entrepreneur will strive to earn the pleasure of Allah by not only aiming to increase wealth, but prioritising mutual benefit and benefit. In the implementative realm, islamic entrepreneurship wil prioritise the comfort of others and not harm each other in order to achieve the concept of life balance as intended by Allah SWT. This article aims to describe the application of islamic entrepreneurship in Sidogiri Islamic Boarding School by examining the values that underlie the pesantren in estabilishing and managing various Islamic Boarding School-owned enterpirses such as Kopontren Basmalah, Bait al-Mal Wa al-Tamwil (BMT) and Santri Mineral Water. The results of this study indicate that all Sidogiri Islamic Boarding School-owned enterprises have practised the principles of islamic entrepreneurship such as hard work in the name of Allah, providing benefits for individuals with good.